Digital Financial Literacy and Green Fintech Adoption Enhancing Sustainable MSME Financial Performance Based on SDGs - Heni Purwantini; Hasirun Hasirun; Juli Handayani; Meliana Cintia Sari (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This community service-based study examines the implementation of Digital Financial Literacy and Green Fintech Adoption programs to improve the Sustainable Financial Performance of MSMEs in Indonesia within the Sustainable Development Goals (SDGs) framework. Methodology: A quantitative survey approach was applied, involving 600 MSMEs across several Indonesian provinces. Community empowerment activities include digital financial literacy assistance, green fintech education, and sustainability-oriented business mentoring. Data were analyzed using the SEM-PLS with SmartPLS 3.0. Results: The findings indicate that Digital Financial Literacy and Green Fintech Adoption positively and significantly improve Sustainable Financial Performance. Sustainable Business Practices mediate the relationship between digital capabilities and financial performance, while Government Support strengthens the relationship between sustainable practices and financial outcomes. Conclusions: Community service interventions focusing on digital financial capability development, green fintech utilization, and sustainability-oriented business mentoring effectively enhance MSMEs’sustainable financial performance. Government support also strengthens the effectiveness of sustainability programs. Limitations: This study is limited by its cross-sectional design and self-reported data from MSMEs that participated in digital financial service programs. Contributions: This study extends the Dynamic Capabilities Theory in the context of community empowerment, digital finance, and sustainable MSME development while providing practical implications for policymakers and MSME practitioners.